Examining the relationship of psychological well-being with religious orientation and forgiveness among students at the University of Mohaghegh Ardabili - Esmaeil Sadri Damirchi; Nasim Mohammadi; Mina Fayazi; Ebrahim Afsar (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objective: Given the rise of positive-thinking approach to mental health in recent years, Psychological well-being, which is a measure for the growth of the real talents of each individual, has attracted scientific attention. This study aimed to investigate the relationship of psychological well-being to religious orientation and forgiveness among students at the University of Mohaghegh Ardabili. Methods: The descriptive and correlational method was used in this study and the statistical population consisted of students of mohaghegh Ardabili University in 2015. 150 students were selected using available sampling method. The subjects were inquired to answer the Ryff's Psychological Well-being questionnaire, Alport religious orientation questionnaire and Walker and Garsokh Forgiveness Scale. Multiple regression analysis was used to analyze the data. All ethical issues were observed. Moreover, the authors did not report conflict of interest. Results: The findings proved that there is a positive significant relationship between psychological well-being with intrinsic religious orientation and Forgiveness as well as negative significant between psychological well-being and external religious orientation among students (p<0/01). Conclusion: Therefore, It can be concluded that attention to religious orientation and efforts to promote forgiveness in students can improve their psychological well-being. For downloading the full-text of this article please click here.